Hybrid Force-Based Model to Simulate Behavior of Human Crowd in Panic Situations- - Ammar Alnahhas; ElisaarBarri (Journal of Digital Information Management, 2019)
Modelling human behavior is important as it helps preparing for the situation of emergency to save lives. In this paper we present new methods to simulate crowd evacuation phenomena by using a physical model. We focus on applying more effective forces focusing on Spring-Force as general forces affecting agents as well as repulsive danger-force, in addition, we propose a new algorithm for an interaction behavior. We implement our algorithm in a real-world application which shows that our model provides results approaching reality and is promising compared to the other models.